Pelatihan Model Guru Favorit di Mata Siswa Milenial Untuk Guru Sekolah Menengah Dengan Menggunakan Dasar Hasil Penelitian - Ignatius Ario Sumbogo (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2022)
Community Service Activities are one of the dharmas that are bound as a downstream of research results. This PKM activity is built on the results of research that has been carried out in collaboration with PT Erlass Prokreatif Indonesia partner, which operates as a course and training institution at the secondary school level, with 80 teachers spread across various provinces on the island of Java. The PKM activity uses the Training method with the theme: Creating a Favorite Teacher Figure in the Eyes of High School Students which will be held online on August 29, 2021, initiated by Partners. This PKM activity aims to build a new understanding among high school teachers regarding the figure and character of a favorite teacher in the eyes of millennial generation school students, which can improve the quality of learning in particular to be more effective and efficient. This is motivated by a shift in views among millennial generation students on the figure of an educator that can be accepted by them. There are several variables that are emphasized referring to changing times, namely Social Media Engagement, Services, Attitudes and Student Perceptions with the dependent variable being student learning motivation. The results of the PKM show the enthusiasm of high school teachers to improve themselves in some of these aspects in order to become a figure with a favorite image among students because it makes it easier for the teaching and learning process to be effective and efficient.